SISTEM INFORMASI PENDATAAN PENDUDUK MENGGUNAKAN METODE CANVASSER PADA DESA KEBONSARI KECAMATAN ROWOSARI - Siti Rofiah (STEKOM PRESS, 2018)
The main purpose of conducting research is to design a system of information on population data collection in the process of processing population data, data on population entry, data on population moving, births, and deaths in Kebonsari Village, Rowosari District. The method used by the author is in accordance with the population data collection method used in Kebonsari Village, using the canvasser method with Visual Basic, MySQL and Crystal Report Software. The results of the study are expected to use a computerized population data collection system that is inputting data, searching data, making reports, and making population documents will be easier because data is stored in a database and data security is guaranteed. Keywords: Information systems, population data collection, canvasser methods. Abstract The main objective of the research is to design a population data collection information system in the process of processing population data, incoming population data, moving population data, births, and deaths in Kebonsari Village, Rowosari District. The method used by the author is in accordance with the population data collection method used in Kebonsari Village, namely the canvasser method using Visual Basic Software, MySQL and Crystal Report. The results of the research are expected to use a computerized population data collection system. Data input, data search, report generation, and population registration will be easier because data is stored in databases and data security is guaranteed.